Association of Urinary Phthalate Metabolites With Erectile Dysfunction in Racial and Ethnic Groups in the National Health and Nutrition Examination Survey 2001-2004. (May 2017) - Lopez, David S.; Advani, Shailesh; Tsilidis, Konstantinos K.; Wang, Run; Baillargeon, Jacques; Dobs, Adrian; Symanski, Elaine; Canfield, Steven
Phthalates are endocrine-disrupting compounds detectable in more than 75% of the U.S. population with differential distributions across racial and ethnic groups, and they have been linked with reduced levels of serum testosterone. This study aims to investigate the associations of phthalate metabolites with erectile dysfunction (ED) and to determine whether these associations vary by race/ethnicity among men in the United States. Analyzed data for 12 phthalate metabolites from 3, 746 men (≥20 years old), who participated in the National Health and Nutrition Examination Survey 2001-2004 cross-sectional study, were included. Metabolites included MBP, MCHP, MEP, MEHP, MiNP, MBzP, MMP, MCPP, MEHHP, MEOHP, MiBP, and MECPP. Racial/ethnic groups included non-Hispanic Blacks ( n = 770), non-Hispanic Whites ( n = 2, 147), and Mexican Americans ( n = 829). ED was assessed by a single question during a self-paced, computer-assisted self-interview. In racial/ethnic stratified analyses, there were higher MBP and MBzP concentrations that had a strong-dose response association with lower prevalence odds of ED among Mexican Americans, p trend < .01, and p trend = .03, respectively. Similarly, a significant inverse association between MEHHP and likelihood of ED among non-Hispanic Black men ( p trend < .04) was observed. Furthermore, significant inverse associations between higher concentrations of phthalates and ED were identified only in minority populations. Further investigations, particularly prospective studies, are warranted to determine the role of phthalates on the biological mechanism(s) associated with ED. A focus may be placed on testosterone levels which are suggested to be affected by phthalates, and also low levels of testosterone are suggested to increase the risk of ED.